Pengaruh model problem based learning terhadap kemampuan literasi matematika materi bangun ruang sisi datar siswa kelas VIII SMPN 13 Mataram tahun ajaran 2024/2025 - Baidowi; As Syifa Umiturrahma; Dwi Novitasari (FKIP Universitas Mataram, 2026)
The problem addressed in this study is the low level of mathematical literacy among eighth-gradestudents at SMPN 13 Mataram regarding flat-sided three-dimensional shapes. This study aims todetermine the effect of the Problem-Based Learning (PBL) model on the mathematical literacy ofeighth-grade students at SMPN 13 Mataram regarding flat-sided three-dimensional shapes. Thisstudy is a quasi-experimental study with a posttest-only control group design. The population inthis study consists of eighth-grade students at SMPN 13 Mataram, comprising 5 classes with atotal of 178 students. The sample in this study consisted of 72 students selected using clusterrandom sampling, resulting in Class VIII C being designated as the experimental class receivingPBL instruction and Class VIII D as the control class receiving Direct Instruction. The researchinstrument was a mathematics literacy test based on three indicators: formulate, employ, andinterpret. Data were analyzed using normality and homogeneity tests, as well as a t-test. Theresults showed a significant difference in the average mathematical literacy skills between ClassC and Class D, with a p-value of 0.0000 and an effect size of 2.75, which falls into the very largecategory. Thus, it is concluded that the PBL model has an effect on the mathematical literacy skillsof eighth-grade students at SMPN 13 Mataram regarding the topic of flat-sided three-dimensionalshapes.